Effectiveness and Safety of a High‐Dose Weekly Vitamin D (20, 000 IU) Protocol in Older Adults Living in Residential Care. Issue 8 (15th July 2014) - Feldman, Fabio; Moore, Crystal; da Silva, Liz; Gaspard, Gina; Gustafson, Larry; Singh, Sonia; Barr, Susan I.; Kitts, David D.; Li, Wangyang; Weiler, Hope A.; Green, Timothy J.
<x xml:space="preserve">Abstract</x> Objectives To report 25 hydroxyvitamin D (25OHD) concentrations, an indicator of vitamin D status, in older adults living in residential care 1 year after a protocol of weekly 20, 000 IU of vitamin D was started. Design Cross‐sectional. Setting Five residential care facilities in British Columbia, Canada. Participants Residents aged 65 and older from five facilities (N = 236). Measurements Participants provided a blood sample. Demographic and health information was obtained from the medical record. Results Mean 25OHD was 102 nmol/L (95% confidence interval (CI) = 98–106 nmol/L). Three percent of residents had a 25OHD concentration of less than 40 nmol/L, 6% <50 nmol/L, and 19% <75 nmol/L. In those who received 20, 000 IU/wk or more for 6 months or longer (n = 147), mean 25OHD was 112 nmol/L (95% CI = 108–117 nmol/L), and none had a 25OHD level of less than 50 nmol/L. Hypercalcemia (>2.6 mmol/L), a potential consequence of too much vitamin D, was present in 14%, although 25OHD levels did not differ in those with and without hypercalcemia (108 vs 101 nmol/L; P = .17). Conclusion Twelve months after implementation of a 20, 000‐IU/wk vitamin D protocol for older adults in residential care, mean 25OHD concentrations were high, and there was no evidence of poor vitamin D status. Given the absence of demonstrated benefit of high 25OHD concentrations to the residential care population, dosages less than 20, 000 IU/wk of vitamin D are recommended.